Libya's flawed unity government: A semblance of compromise obscures old and new rifts - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2021)
The formation of the Government of National Unity (GNU) under Abdelhamid Dabeiba in March 2021 was a breakthrough in efforts to overcome Libya's political division. But the settlement's flaws are already starting to show. So far, political actors have merely agreed to compete for access to state funds within a unified government. Distributive struggles could soon test the government's cohesion. Meanwhile, substantive disagreements are being shoved aside; in particular, the government is trying to ignore the challenges in the security sector. Unless progress is made towards elections that are planned for December 2021, tensions between profiteers and opponents of the government risk provoking a new political crisis. But even the elections themselves harbour potential for renewed conflict.
Keywords: 320